Sanitary Landfilling – A Key Component of Waste Management - Johann Fellner (Jurnal Rekayasa Kimia & Lingkungan)
In many affluent countries waste management is experiencing a fast transition from landfilling to sophisticated recycling and waste to energy plants. Thus, landfilling of waste becomes less important in these countries. The present paper discusses whether a similar development will take place in transition economies, or waste management systems will mainly rely on landfilling in the near future. For this purpose, the current waste management practices and associated environmental impacts as well as the economic situation of different countries in economic transition are analyzed. Based on the status quo, scenarios for improving waste management are developed and evaluated. Criteria for evaluation are economic parameters, and indicators pointing out if the goals of waste management (protection of human health and the environment, the conservation of resources), are reached. Based on the results of selected case studies, it is shown that for regions that can afford less than 20 €/capita and year for waste management, landfilling will remain a key component of waste management, since other disposal options such as waste to energy or mechanical biological pretreatment are too expensive. In addition, the results indicate that in many of these countries waste collection still represents a main challenge.